Assembly of a conductive antimony tin oxide (ATO) polyethersulfone (PES) nano composite thermal insulation film - Baoyan Xing; Honfang Ma; Bingrong Dong; Aijun Li; Jianguo Zhao; Guibin Ma (Scientific Reports)
Abstract Organic-inorganic nano-composite films have attracted considerable attention due to their extraordinary properties, performance and applications. Herein an antimony tin oxide (ATO) polyethersulfone (PES) nano-composite conductive film has been assembled. First, the high conductivity ATO nanoparticles were synthesized in the solid state and fully characterized, focusing on their conductive properties. Next, oleic acid (OA) was selected as a dispersion agent, and the minimum resistance (R) is found at an OA/ATO weight ratio at 0.5 in an NMP solution. Third, the ATO-PES nano-composite films were assembled by mixing a blended solution applied to the OA capped ATO nanoparticle solution with the polymer PES. Five different ATO composited films (4.5, 9.8, 18.8, 28.7 and 32.2%) were prepared under the same conditions but only the 32.2% weight of ATO film showed electronic conductivity at the OA/ATO weight ratio of 0.5. However, the film conductivity is not homogenous, and it becomes more homogenous when the OA/ATO weight ratio is reduced to 0.19 and with 35.8% ATO. The measured top film resistance (R) shows a linear correlation to the film length, indicating that the film resistance is homogenous. The topography and current mapping of the film top shows the root mean square roughness (R q ) of the topography image is around 40 ± 2.5 nm with agglomerates of densely packed ATO nanoparticles embedded into the polymer matrices in the film. The current map indicates that the current is only present where nanoparticles are located. A thermal radiation test showed that the film has excellent thermal insulation properties and potential application in efficient building insulation and as a blocker of solar radiation for tent materials.